Hubungan Kompetensi Dan Kompensasi Dengan Kinerja Pegawai Pada UPTD Puskesmas Mekarsari Kabupaten Lebak Tahun 2024 - Eris Harismasakti; Fardan (Universitas La Tansa Mashiro, 2024)
In the 2023 performance target, the Mekarsari Community Health Center carries a target of 100% in the resulting regional policy plan, as well as for its implementation. The target percentage of the number of Regional Apparatus Organizations (OPD) whose physical realization targets have been completed is 95%. If you look at it, it's certainly a good target. Furthermore, in the 2021 Government Agency Performance Report, the Mekarsari Community Health Center shows that the planned performance target has decreased compared to the performance target in 2023. To determine the influence of competency on employee performance at the Mekarsari Public Health Center UPTD, Lebak Regency in 2024. To determine the influence of compensation on employee performance at the Mekarsari District Public Health Center UPTD. Lebak in 2024. To find out the influence of competency and speed on employee performance at the UPTD of Mekarsari Health Center, Lebak Regency in 2024.This research used a sampling technique, namely Sampling/Saturated Sample